The quality of New Zealand goat meat and the effect of sous vide and microwave processing on its quality and in vitro protein digestibility : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand - Gawat, Mariero (Massey University, 2024)
New Zealand has an untapped goat meat industry that has yet to be developed as a significant source of healthier red meat. However, this meat is known for being tough and requiring longer cooking times to achieve tenderness preferred for household and industrial use. Currently, there are no pertinent data describing the quality of goat meat produced in New Zealand (NZ). Furthermore, processing conditions significantly affect meat quality in terms of protein digestibility and, consequently, nutritional value. This thesis investigated the quality of NZ goat meat and the impact of sous vide and microwave processing on its quality and in vitro protein digestibility. The goat meat produced in NZ are mainly coming from wild goats known as feral goats. In this study, the differences between the quality characteristics of goat meat from NZ feral goats and Boer crosses a popular meat breed were investigated. Our data show that tenderness is highly affected by meat pH, collagen content, and muscle type. Meat from different breeds can be differentiated by colour and feral goat meat had higher collagen content but with lower solubility compared to Boer crosses. Further evaluation of goat meat ultrastructure revealed that the current practice in handling goat meat carcasses results in supercontracted muscle. Regardless of breed, the challenge for goat meat quality includes its inherently high pH and susceptibility to cold shortening, which affect its technological properties. This project also highlights the impact of processing on goat meat structure and protein digestibility. Using a static in vitro digestion system, the protein digestibility of sous vide (SV) cooked goat meat was initially investigated between different breeds. Meat from Boer crossbreeds had higher digestibility than meat from feral goats in terms of the degree of hydrolysis. The level of collagen significantly affected the variability in meat digestion rate, specifically during the gastric phase. Further investigation of the effects of thermal processing on goat meat was also explored by comparing the impacts of sous vide and microwave processing. The sous vide and microwave processed goat meat varied in meat quality and protein structure. However, the difference in the vitro protein digestibility of goat meat as influenced by the processing method was observed in gastric phase. Moreover, peptidomics revealed that sous vide and microwave processing significantly affected the hydrolysis of major proteins in goat meat, but this variation was only apparent in the gastric phase complimenting, the initial protein hydrolysis data. Overall, this research provided new information on the physicochemical properties, muscle structure, and protein digestibility of goat meat as affected by breed, muscle type, and processing conditions. The outcomes provide significant knowledge about New Zealand goat meat quality and highlight the role of muscle structure and pH for its quality improvement. Protein digestibility studies also revealed that the effect of different processing conditions on meat protein digestibility was evident only in the gastric phase.
Keywords: in vitro protein digestion; meat science; meat processing; meat structure; 300607 Food technology